Shri Baburao Govindrao Shirke-An Industrialist - ., . (Journal of Engineering Education Transformations, 1995)
Started in a humble way by establishing his own construction company, B. G. Shirke & Co., about 50 years ago. The firm executed a large number of specialised constructions covering residential, industrial, institutional and commercial structures, Strategic Defence Installations mostly using conventional methods and materials.